The Study of Propolis, Pollen, and Royal Jelly Enrichment at Honey Product as Natural Antioxidant (Jurnal Ilmu dan Teknologi Hasil Ternak, 2007)
The research was carried out in the Milk Pilot Plant Laboratory, Brawijaya University Malang from October to November.The objective of this research was to determine antioxidant activity of honey enrichment by Propolis, Pollen, and Royal jelly. Indicator of antioxidant activity is peroxide number. Lower peroxide number indicated that this product has higher antioxidant activity.The result of this research was the honey enrichment by Propolis 480mg, pollen 320mg and royal jelly 480mg decrease 0.2333 meq peroxide number. Effect of added proportion of 0.5ml; 1ml; 1.5ml honey formulation into 3.5 ml oil oxidation substrate has peroxide number by 0.5167 meq; 0.3667 meq; and 0.2333 meq. It can be concluded that the addition various formulation combine show highly significantly different effect (P<0,01)on peroxide number in oil substrate. Â  Keywords : propolis, royal jelly, pollen, honey, antioxidant